Head–Eye Vestibular Motion Therapy Affects the Mental and Physical Health of Severe Chronic Postconcussion Patients - Carrick, Frederick Robert; Clark, Joseph F.; Pagnacco, Guido; Antonucci, Matthew M.; Hankir, Ahmed; Zaman, Rashid; Oggero, Elena (Frontiers in Neurology, 2017)
Context Approximately 1.8–3.6 million annual traumatic brain injuries occur in the United States. An evidence-based treatment for concussions that is reliable and effective has not been available. Objective The objective of this study is to test whether head–eye vestibular motion (HEVM) therapy is associated with decreased symptoms and increased function in postconcussive syndrome (PCS) patients that have been severely impaired for greater than 6 months after a mild traumatic brain injury. Design Retrospective clinical chart review. Setting and participants Tertiary Specialist Brain Rehabilitation Center. Interventions All subjects underwent comprehensive neurological examinations including measurement of eye and head movement. The seven modules of the C3 Logix Comprehensive Concussion Management System were used for pre- and postmeasurements of outcome of HEVM therapy. Materials and methods We utilized an objective validated measurement of physical and mental health characteristics of our patients before and after a 1-week HEVM rehabilitation program. We included only PCS patients that were disabled from work or school for a period of time exceeding 6 months after suffering a sports concussion. These subjects all were enrolled in a 5-day HEVM rehabilitation program at our Institutional Brain Center with pre- and post-C3 Logix testing outcomes. Results There were statistical and substantive significant decreases in PCS symptom severity after treatment and statistical and substantive significant increases in standardized assessment of concussion scores. The outcomes were associated with positive changes in mental and physical health issues. This is a retrospective review and no control group has been included in this study. These are major limitations with retrospective reviews and further investigations with prospective designs including a randomized controlled study are necessary to further our understanding. Conclusion Head–eye vestibular motion therapy of 5 days duration is associated with statistical and substantive significant decreases of symptom severity associated with chronic PCS.